Missing Teeth and Sticky Parts of Urban Plans: The Case of Patrick Geddes’ Tel Aviv - Cem Kayatekin (Environmental Science and Sustainable Development)
This paper is focused on the rise, development, and current state of the built environment of Tel Aviv, specifically looking at (1) the historical context within which Tel Aviv’s origin story is situated; (2) the ideals initially espoused by Patrick Geddes in his master plan for the city, and how the built environment mutated as varying pressures began to push and pull at its seams in the decades that followed; (3) the parts of the initial master plan which maintained their tenacity within the built environment, in comparison to the parts which were absorbed by the weight of rapid urbanization; and (4) the unexpected micro-architectural typologies that have emerged within the built environment of Tel Aviv, anchored within the micro-scale urban morphological niches framed by Geddes’ original master plan. The first two points, located within the discursive landscape of architectural and urban history, are addressed via a historical methodological approach. The latter two points are scrutinized via an analysis of the contemporary built environment of Tel Aviv, with the final point specifically utilizing an ideal-type analysis often deployed within psychological and sociological research. The findings presented across the paper are in close relationship with the growing body of literature attempting to partially steer the discursive landscape concerning Tel Aviv away from an obsessive focus on the city’s modernist architectural legacy and towards a deeper understanding and recognition of what has pejoratively been deemed the background fabric of the city.